2019
DOI: 10.18632/oncotarget.26676
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypomethylation-related overexpression of SFN, GORASP2 and ZYG11A is a novel prognostic biomarker for early stage lung adenocarcinoma

Abstract: Although alteration of DNA methylation in advanced cancer has been extensively investigated, few data for early-stage lung adenocarcinoma are available. Here, we compared DNA methylation profiles between adenocarcinoma in situ (AIS) and early invasive adenocarcinoma using the Infinium methylation array to investigate methylation abnormalities causing early progression of adenocarcinomas. We focused on differentially methylated sites which were located in promoter CpG islands or shore regions, and identified 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(41 reference statements)
1
11
1
Order By: Relevance
“…Previously, we examined the gene expression profiles of early stage lung adenocarcinomas and identified stratifin (SFN, 14‐3‐3 sigma), which showed significantly higher expression in small but invasive lung adenocarcinoma (tumor size less than 3 cm in diameter) than in adenocarcinoma in situ or normal lung . Overexpression of SFN is due to DNA hypomethylation in its promoter region and is associated with poor patient outcome in lung adenocarcinoma . We have found that suppression of SFN reduces cell proliferation in vitro and tumor formation or metastasis in vivo, suggesting that SFN facilitates tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we examined the gene expression profiles of early stage lung adenocarcinomas and identified stratifin (SFN, 14‐3‐3 sigma), which showed significantly higher expression in small but invasive lung adenocarcinoma (tumor size less than 3 cm in diameter) than in adenocarcinoma in situ or normal lung . Overexpression of SFN is due to DNA hypomethylation in its promoter region and is associated with poor patient outcome in lung adenocarcinoma . We have found that suppression of SFN reduces cell proliferation in vitro and tumor formation or metastasis in vivo, suggesting that SFN facilitates tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Additional functional validation in sex-stratified models will be needed to test the gender specific roles of ZYG11A variants. High levels of ZYG11A are associated with advanced lung adenocarcinoma and drives cellular proliferation in part via upregulation of cyclin E to promote tumorigenesis (Husni et al, 2019;Wang et al, 2016). Recent studies implicated ZYG11A as downstream of the IGF-1 pathway in p53 wild-type cancer cells (Achlaug et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hypomethylation mechanisms include disruption and loss of DNA methylation affecting genomic integrity and stability [ 4 ]. Some genes, such as GORASP2, ZYG11A, and SFN, are significantly hypomethylated in LC adenocarcinoma [ 9 ].…”
Section: Dna Methylation In Tumorigenesismentioning
confidence: 99%
“…Most of the LC are related to DNA hypermethylation, however, some genes (GORASP2 and ZYG11A) are hypomethylated and overexpressed in invasive adenocarcinoma. Thus, there is a large field for the development of new prognostic indicators and potential novel target molecules for clinical applications [ 9 ].…”
Section: Clinical Role Of Mirnas In Diagnosis Prognosis and Treatmenmentioning
confidence: 99%